Assessment of Depression Among Older Adults Staying in Old Home Care in Klang, Malaysia - Qamar, Muhammad; Zahirah, Nurul; Ahmad, Sohail (UI Scholars Hub, 2020)
Mental disorders such as depression are widespread, often underdiagnosed, and usually inappropriately treated. The early recognition of factors that may promote depression with the help of depression screening aid can help to plan better care for the patient. Therefore, this study aimed to determine the depression prevalence among the older adults staying in old home care, to explore any association and differences of depression across various socio-demographic variables, and to study the predictors of depression among study subjects. A cross-sectional study was conducted with a convenience sample of 141 elderly by using the validated tool. The study instrument was divided into two sections: Section I (Socio-demographic data); Section II (M-Geriatric Depression Scale-14). The results showed 44.7% were in the age group of 65-75 years, the majority were Chinese (42.6%), and male (57.4%). Among the subjects, 43.3% had hypertension, followed by 39% of diabetes, and 8.5% were with heart disease, while more than 90% reported not known history of depression. The study revealed that more than 50% of the respondents had depression. Statistically, a significant difference was observed between the depression prevalence with marital status (p=0.021) and a history of heart disease (p= 0.002). On multivariate analysis, heart disease was found to be statistically significant. Depression was prevailing among the older community those who were staying in old home care. Daily evaluation should be done for the older population staying in old home care to attenuate the prevalence of depression. Family and social support were vital to highlight the issue of depression among older adults.